WHEN A PERSON LOSES THE FREEDOM IN FRONT OF AN INTERNATIONAL ORGANIZATION. WHAT TO DO? (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
What happens when a person is unfairly accused of terrorism by an international organization against which you cannot defend yourself? What mechanisms exist when there are no defense procedures against an organization consisting only of states? If the UN is a state and nationoriented organization, how can a person be accused of terrorism? How is humanitarian law activated? Is there freedom in such cases?